Peran komunikasi internal dan kepemimpinan pada karyawan di PT Allo Bank Indonesia (studi kasus Allo Bank Trans Studio Mall Cibubur) - Dindawati, Dea; Permata, Widiana Indah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study aims to analyze the role of internal communication and leadership style in enhancing employee productivity at PT Allo Bank Indonesia, Trans Studio Mall Cibubur branch, through the perspective of George Herbert Mead’s Symbolic Interactionism Theory. The findings reveal that internal communication plays a crucial role in fostering shared understanding through message clarity, meaning clarification, and feedback from subordinates. Leadership is not solely interpreted from formal attributes but also from attitudes, consistency, and communication style that foster employee loyalty and motivation. Moreover, misinterpretations of verbal and nonverbal symbols are perceived as part of the learning process, encouraging greater caution and adaptation in communication. Symbolic meanings such as uniforms, communication style, and daily interactions contribute to the creation of shared meanings that strengthen work coordination.